2014
DOI: 10.1016/j.tet.2014.05.073
|View full text |Cite
|
Sign up to set email alerts
|

A mild and efficient AgSbF6-catalyzed synthesis of fully substituted pyrroles through a sequential propargylation/amination/cycloisomerization reaction

Abstract: Development of an efficient synthesis of fully substituted pyrroles via a sequential as a catalyst. The propargylation/amination/cycloisomerization was accomplished using AgSbF6 one-pot three-component reaction of propargylic alcohols, 1,3-dicarbonyl compounds, and primary amines proceeds at a mild temperature, which prevents the formation of furan by-product. The reaction was also successfully applied to the more basic aliphatic amines with the addition of 1.1 eq. of acetic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Initial AgSbF 6 -catalyzed dehydrative addition of 1,3-dicarbonyl compounds was followed by treatment with anilines to provide a range of penta-substituted pyrroles in good to excellent yield over two steps. 88 The authors demonstrated that alkylamines can replace anilines in this procedure, albeit under much harsher reaction conditions. Pan, Zhang and co-workers reported the Cu(OTf) 2 -catalyzed dehydrative addition of styrene derivatives to propargylic alcohols, 89 advancing earlier work by Wang and co-workers who reported the same system using FeCl 3 as a catalyst, 90 but were limited to the more potent 1,1-diarylalkenes as nucleophiles in this ene-type reaction (Table 4, entries 10 and 11).…”
Section: Syn Thesismentioning
confidence: 99%
“…Initial AgSbF 6 -catalyzed dehydrative addition of 1,3-dicarbonyl compounds was followed by treatment with anilines to provide a range of penta-substituted pyrroles in good to excellent yield over two steps. 88 The authors demonstrated that alkylamines can replace anilines in this procedure, albeit under much harsher reaction conditions. Pan, Zhang and co-workers reported the Cu(OTf) 2 -catalyzed dehydrative addition of styrene derivatives to propargylic alcohols, 89 advancing earlier work by Wang and co-workers who reported the same system using FeCl 3 as a catalyst, 90 but were limited to the more potent 1,1-diarylalkenes as nucleophiles in this ene-type reaction (Table 4, entries 10 and 11).…”
Section: Syn Thesismentioning
confidence: 99%
“…In 2014, Zheng reported an one-pot three-component reaction for the preparation of fully substituted pyrroles catalyzed by AgSbF 6 (Scheme 24). 31 In this reaction, propargylic alcohols, 1,3-dicarbonyl compounds, and primary amines were included to construct fully substituted pyrroles via a sequential propargylation/amination/ cycloisomerization under mild conditions. And, with the addition of acetic acid, many basic aliphatic amines could be tolerated in this methodology.…”
Section: Ag-catalyzed Synthesis Of Pyrroles From Internal Alkynesmentioning
confidence: 99%
“…Acetonitrile (CH 3 CN), 1,2-dichloroethane (1,, and nitromethane (CH 3 NO 3 ) were previously shown to be compatible solvents for the formation of 3a. 9 However, they were less effective when compared to toluene as the solvent for the following cycloisomerization reaction.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Recently, we reported a straightforward AgSbF 6 -catalyzed one-pot synthesis of fully substituted pyrroles (4) via propargylation of 1,3-dicarbonyl compounds (2) with propargylic alcohols (1) to form 3, followed by amination with primary amines and cycloisomerization. 9 We observed that when aliphatic amines were used, likely due to the basicity of the amines, significant amount of fully substituted furans 5 was formed as a by-product (Scheme 1). These observations prompted us to explore the use of AgSbF 6 for the furan formation, in the context of expanding the arsenal of highly efficient syntheses of heterocycles.…”
Section: Introductionmentioning
confidence: 95%